[OA089] Diffusing Alpha-emitters Radiation Therapy (DaRT): template based treatment planning technique for brachytherapy of squamous cell skin cancer. (August 2018) - Feliciani, Giacomo; Bellia, Salvatore Roberto; Bianchini, David; Mazzotti, Giorgio; Ravaglia, Valentina; Keisari, Yona; Popovtzer, Aaron; Kelson, Itzhak; Monti, Manuela; Duca, Massimo Del; Turri, Valentina; Stanganelli, Ignazio; et al.
Abstract : Purpose: The Diffusing Alpha-emitters Radiation Therapy (DaRT) is a novel brachytherapy technique employing 224-Radium enriched seeds releasing short-lived alpha-emitting atoms into the tumor[1] . 1 st patient in Europe was enrolled and treated at IRST and medical physicists provided a tool to plan the brachytherapy treatment in order toimprove the precision and safety of seed insertion. Methods: Given the novelty of the technique we refer to an article for its general description (1). The patient underwent a 18-FDG PET ⧹ CT for both metabolic uptake control and lesion definition. A sterile patch was applied on the skin lesion just before the image acquisition and an adhesive fiberglass mesh (spaced by 2 mm) tape was then placed above. The Radiotherapist contoured the lesion and marked possible entrance points for the needles with a radio opaque ink marker. According to the radio opaque marks and metabolic uptake the CTV was defined and with any commercial brachytherapy TPS it is possible to simulate and adjust the spatial seeds distribution. The method described was previously tested on home-made phantom. Before the treatment the template was placed again on the patient and seeds were inserted accordingly to the plan using special applicators. Finally, correct positioning of the seeds was checked again with a post-treatment CT scan. Results: The template was correctly placed in position and it was clearly visible in CT(fig1). Through the TPS it was possible to visualize entrance points for the applicator as suggested by the radiotherapist and eventually improve the coverage of the tumor by adding additional seeds. The post-treatment CT allows to evaluate the correspondence between the planned and actual seeds position. Conclusions: The procedure implemented in IRST is robust and complete; the method for template definition is a promising tool supporting the Radiotherapoist for precise and safe DaRT delivery.